A pilot investigation using global positioning systems into the outdoor activity of people with severe traumatic brain injury - Clark, Ross A; Weragoda, Natasha; Paterson, Kade; Telianidis, Stacey; Williams, Gavin (Journal of neuroengineering and rehabilitation, 2014)
Little is known about the post-discharge outdoor activities of people who have incurred severe traumatic brain injury (TBI). This study used a body-worn global positioning system (GPS) device to determine the outdoor activity per day performed by this population. Additionally, this study examined the association that mobility, time since injury and injury severity had with levels of outdoor physical activity. Seventeen people with TBI and 15 control subjects wore a GPS device for between 3-7 days to monitor their outdoor activity. Based on the individual's location and speed of movement the outdoor physical activity in minutes per day was derived. Assessments of duration of outdoor activity between groups, and the relationship that duration of outdoor activity had with results on the high-level mobility assessment tool, length of post-traumatic amnesia, and time since injury were performed. No significant (p = 0.153, effect size = 0.26) difference in time spent in outdoor physical activity was observed between the TBI (median[IQR] = 19[3-43]mins) and control (median[IQR] = 50[18-65]mins) group. Interestingly, 35% of TBI subjects performed <10 mins of outdoor activity per day compared to 13% of the control group. The TBI group also recorded three of the four highest values for outdoor physical activity. Higher levels of mobility were associated with more outdoor activity (Spearman's rho = 0.443, p = 0.038). No other significant associations were observed. While preliminary, our results indicate that a sub-group of people with TBI exists who restrict their outdoor activities. GPS has potential as an activity tracking tool, with implications for rehabilitation and exercise prescription.